Principles of project finance - Yescombe, E. R. (Amsterdam ; Boston : Academic Press, 2002)
This introduction for practitioners offers a balanced view of project financing, integrating legal, contractual, scheduling, and other areas that participate in large multiparty projects, large single-asset purchases, and broad-based financing programs for fleets of assets. It mixes theories and case studies but avoids becoming too oriented toward applications in any one particular industry. It focuses on the concepts and techniques required by project finance people without being overly academic or beset by case studies.
oif 19/03/15
Loan
Keywords: Project management -- Finance